Response of wheat to phosphorus fertilization on an oxisol - Fageria, Nand Kumar (Pesquisa Agropecuaria Brasileira, 2014)
Phosphorus deficiency is one of the most important growth limiting factors in crop production in oxisols under cerrados of central Brazil. The objective of this study was to evaluate the effect of P fertilization on growth, yield and nutrients uptake by wheat in a dark-red latosol under greenhouse conditions. The P treatments applied were 0, 25, 50, 75, 100, 125, 150, 175 and 200 mg P/kg-1 of soil. Root dry weight and grain yield were significantly affected by P fertilization. Adequate P level for dry matter production was about 75 to 100 mg of P/kg-1, of soil, whereas for grain yield it was about 175 mg of P/kg-1 of soil. Distribution of nutrients in different plant parts showed roots retaining maximum Fe; tops maximum K, Ca, Mg and Mn; grains maximum P and considerable amount of Mg and Zn. Concentrations of Ca and Mg increased with P fertilization, but Zn, Fe and Cu contents of plant tops decreased with increasing levels of P.